Osteogenic induction of menstrual blood mesenchymal stem cell by different Ferula species extracts - Razieh Dalirfardouei; Elahe Mahdipour; Mehrdad Iranshahi; Khadijeh Jamialahmadi (Mashhad University of Medical Sciences, 2021)
Objective: Ferula spp. have many applications in complementary medicine and are recognized as the most important sources of natural products for bone health and regeneration especially in postmenopausal women. Therefore, the aim of this study was to investigate the effects of the extracts from three Ferula species on proliferation and osteogenesis potential of human menstrual blood-derived mesenchymal stem cells (MenSCs). Materials and Methods: The possible cytotoxic activity of three members of Ferula spp. (at concentrations of 5 to 100 μg/ml) was determined using MTT (3-(4, 5-dimethylthiazol-2-yl)-2, 5-diphenyl tetrazolium bromide) assay. Alkaline phosphatase (ALP) activity assay, Alizarin Red-S staining, and the expression analysis of an osteoblastic gene were performed to evaluate osteogenic differentiation potential. Results: The extracts of F. flabelliloba and F. szowitsiana decreased the viability and growth of MenSCs while F. foetida increased the proliferation of cells after 72 hr incubation. Treatment of MenSCs with selected plant extracts revealed that F. foetida and F. szowitsiana could enhance the osteogenic potential of MenSCs in terms of ALP activity. The Runx-2 expression in the presence of F. foetida was significantly greater than observed following treatment with 17β-estradiol (as positive control). Conclusion: The results of this study suggest that F. foetida and F. szowitsiana may have therapeutic values as a nutraceutical with respect to their considerable influence on osteogenic potential of mesenchymal stem cells.